Предмет: Математика,
автор: kivisow
-9(5-а)+3(-2а-2)-7(-9+а) Раскрой скобки и упрости выражение
Ответы
Автор ответа:
3
Решение:
- 9 (5 - а) + 3 (- 2а - 2) - 7 (- 9 + а) =
= - 45 + a - 6a - 6 + 63 - a =
= (- 45 - 6 + 63) + (a - 6a - a) =
= 12 + (- 6a) =
= 12 - 6a.
Ответ: 12 - 6a.
____________________
Удачи Вам! :)
Похожие вопросы
Предмет: Русский язык,
автор: СофияНемальцева
Предмет: Русский язык,
автор: gbplfnegfz
Предмет: Русский язык,
автор: baleksvl
Предмет: Математика,
автор: netyosa05
Предмет: Алгебра,
автор: гриип